ANALYSIS OF ARABIC FINAL SEMESTER ASSESSMENT QUESTIONS BASED ON MODERATE ORDER THINGKING SKILSS (MOTS) AT MTS ITTIHAD SAMARINDA - Ihsan, Muhammad; Ardiansyah, Muhammad; Amalia, Jessica Noer; Qomari, Nur; Shofura, Syifa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Evaluation of learning is crucial in education to measure student achievement and provide feedback to students and educators. Evaluation must adhere to the principles of comprehensiveness, continuity, and objectivity. One method to assess learning quality is through the end-of-semester examination (PAS). This research highlights the importance of Moderate Order Thinking Skills (MOTS) in developing students' cognitive abilities, particularly in Arabic language learning. MOTS helps students understand and apply lesson content. This study analyzes Arabic PAS questions for eighth-grade students at MTs Ittihad Samarinda based on MOTS. The research aims to evaluate PAS question quality and provide a basis for future improvements, enhancing the quality of Arabic learning. A descriptive qualitative approach is used to understand phenomena deeply. The content analysis method is applied to relevant documents and records. The primary data source is Arabic PAS questions for the 2023/2024 academic year at MTs Ittihad Samarinda, collected through documentation and interviews. Analysis of 40 PAS questions shows 32.5% are LOTS, 57.5% are MOTS, and 10% are HOTS, focusing on Arabic syntax and vocabulary. This suggests PAS questions are geared towards understanding and application (MOTS) rather than analysis and evaluation (HOTS). Future PAS question development should balance LOTS and MOTS for junior high school level to improve assessment quality.